Exigência de fósforo para tambaqui (Colossoma macropomum) em diferentes faixas de preço - SOUSA, Thalles José Rego de (2017)
Phosphorus is one of the most limiting essential minerals in plant ingredients. Considering the lack of information regarding the requirement of phosphorus in rations during the different stages of creation, the objective was to evaluate the requirement of phosphorus in rations for tambaqui (Colossoma macropomum) fingerlings and juveniles. In both phases, the treatments consisted of six isoproteic, isoenergetic and isocalcium diets with different digestible phosphorus levels (0,12; 0,33; 0,54; 0,75; 0,95; e 1,16%). In the first phase were used 900 fingerlings of tambaquis with initial weight of 0.51 ± 0,06g, and in the second ere used 300 juveniles of tambaquis with initial weight of 26,4 ± 0,68g. It was adopted a randomized design, with six treatments (phosphorus levels), five replicates per treatment. In the first phase, there was linear effect (P<0,05) on the consumption of digestible phosphorus and quadratic effect (P<0,05) on the weight gain and feed conversion in function the elevation of the digestible phosphorus levels in the diet, estimating the requirement of digestible phosphorus in 0.64% and 0.70%. The daily body deposition of ashes and phosphorus were also influenced in a quadratic (P<0,05) manner as a function of the elevation of the levels of digestible phosphorus of the ration, estimating the requirement in 0.70%; 0.71% respectively. In the second phase the feed intake linearly (P<0,05) increased and digestible phosphorus intake was affected in a quadratic model (P<0,05) in function the increase of digestible phosphorus levels in the diet. The elevation of the levels of digestible phosphorus in the diet provided a quadratic effect (P<0,05) on the weight gain and feed conversion, however, the Linear Response Plateau model was the one that best fit the first variable estimating the digestible phosphorus requirement by 0.46%. The body daily deposition of ash and phosphorus, and body phosphorus retention were also influenced in a quadratic manner. However, the Linear Response Plateau model was the best fit for the first two variables, estimating the phosphorus requirement in 0.33% and 0.45%, respectively. The recommendation of levels of digestible phosphorus in rations for tambaqui fingerlings to optimize weight gain and body phosphorus deposition is 0.71%, which corresponds to the estimated level of 1.04% of total phosphorus.The recommendation of the level of digestible phosphorus in rations for tambaqui juveniles to optimize weight gain and body phosphorus deposition is 0.45%, which corresponds to the estimated level of 0.77% total phosphorus.